Biosensors in diagnosing COVID-19 and recent development (2020)
The outbreak of Coronavirus was first reported from Wuhan, Hubei, China on the end month of 2019. Due to its rapid outbreak and quick transmission, the World Health Organization (WHO) declared it as an ongoing pandemic. Presently, available medicines for viral influenza are found to be ineffective in treatment and there is immediate need of strong technology to detect and monitor public health [91]. Early, notification on symptoms of disease is necessary and can be control up to some extent from this dreadful disease. If monitored in early stage, the infected person can undergo different therapeutic approaches. In order to scan the early symptoms of covid-19 different system has been applied. Use of sensor is considered as one of the method. Sensors when combine with a systematic device, it is utilized to detect the chemical compound and further combines with a biological component with a physicochemical detector. This biosensing system can be included in smart band, optical sensor, plasmonic photothermal sensor, wearable sensor, cell-based sensors, and nano-sensor which can be used to diagnose the COVID-19. Therefore, it is discussed thoroughly in this review with its recent development and future scope on detecting COVID19.